Gender Issues in the Light of Rahner's Theological Perspective - Dallavalle, Nancy (Philosophy & theology, 2014)
Rahner’s work offers several starting points for Catholic theology’s necessary conversion on gender issues. His theology of the symbol sets the stage for an analysis of how “woman” functions in theological anthropology, and for a discussion of how “male” and “female” should be understood in the light of the critique of feminist thought. In short, how do we understand symbols, theologically, as expressive? Linking Rahner’s day and ours, I will then consider how Marian themes were treated by Lumen Gentium and Sacrosanctum Concilium, and how ecclesial questions since then further illustrate the ongoing struggle over the symbol “woman.” Finally, Rahner’s approach to conversion will be employed, as a way of illustrating the intimacy and ubiquity of sexism, given his sense that conversion engages not only isolated actions, but “the whole human being.”